The relationship between primary maladaptive schemas and clinical symptoms of borderline personality disorders and antisocial personality in conscripts: network modeling - Masoumeh Mahboubi; Mahdiyeh Salehi; Amir Mohsen Nedjat (علوم و فنون نظامی)
Objective: The research conducted in military environments has shown that among the soldiers on duty, the most problematic mental disorders are related to antisocial and borderline personality disorders; Therefore, considering the importance and role of schemas in personality disorders, the aim of this study is to investigate the relationship between primary maladaptive schemas and clinical symptoms of borderline personality disorders and antisocial personality in soldiers: network modeling.Methodology: The working method of the current research was descriptive-correlation and network modeling. The target community in the current research is the community of soldiers. The sample of the present study was selected according to the available non-random method of 500 people.Findings: The findings showed that considering that the square of the Pearson correlation coefficient indicates the amount of common variance between the questions, considering the limit of 0.5 means that in order to identify a significant relationship between the nodes, at least the common variance of the nodes in question should be equal to 0.25.Originality: The results showed that among the components presented in the initial maladaptive schemas, the components of abandonment/instability and trapped/untransformed self had the highest amount of extroversion index on average. Also, in the syndromes of borderline and antisocial personality disorders, both antisocial and borderline components have an equal amount of extroversion index.